Heart and soul : the therapeutic face of philosophy - Mace, Chris, 1956- (Routledge, 1999)
"As pyschotherapies continue to proliferate, it has never been more important for the basic assumptions of psychotherapeutic practice to be clarified and reassessed. Heart and Soul shows psychotherapists, philosophers and general readers how an understanding of philosophical themes can transform the ways in which clinical issues are thought about and how psychotherapy is conducted." "Writers who have grappled with the practical implications of major philosophical interests - including ancient philosophy, positivism, existentialism, scepticism, Buddhism, hermeneutics, formal logic and linguistic philosophy - present resumes of relevant ideas and discuss their implications for the consulting room. Their discussions of the nature of psychotherapeutic theory, thinking, technique, relations and language raise issues of considerable philosophical interest."--Jacket